2019
DOI: 10.1093/eurheartj/ehz767
|View full text |Cite
|
Sign up to set email alerts
|

Real-world risk of cardiovascular outcomes associated with hypertriglyceridaemia among individuals with atherosclerotic cardiovascular disease and potential eligibility for emerging therapies

Abstract: Aims Hypertriglyceridaemia in patients with atherosclerotic cardiovascular disease (ASCVD) has been in focus following the REDUCE-IT trial showing benefit with icosapent ethyl. Among individuals with prevalent ASCVD, we sought to quantify the contemporary, real-world risk of ASCVD events associated with hypertriglyceridaemia, as well as estimate icosapent ethyl eligibility and compare trial participants with REDUCE-IT-like individuals in the population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 25 publications
2
59
0
Order By: Relevance
“…Whether or not triglycerides are involved in the atherosclerotic process is still debated. Some data strongly suggest a relation between elevated triglyceride levels and cardiovascular disease [ 41 , 42 ] with a residual cardiovascular risk associated with triglycerides in patients with type 2 diabetes who have reached their LDL-cholesterol target [ 43 , 44 ]. A major role of the retention of cholesterol-rich and triglyceride-rich apoB-containing remnants within the arterial wall is to be considered in the pathogenesis of atherosclerosis [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whether or not triglycerides are involved in the atherosclerotic process is still debated. Some data strongly suggest a relation between elevated triglyceride levels and cardiovascular disease [ 41 , 42 ] with a residual cardiovascular risk associated with triglycerides in patients with type 2 diabetes who have reached their LDL-cholesterol target [ 43 , 44 ]. A major role of the retention of cholesterol-rich and triglyceride-rich apoB-containing remnants within the arterial wall is to be considered in the pathogenesis of atherosclerosis [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with our findings, a recent Canadian realworld study has found that approximately 25% of patients with atherosclerotic cardiovascular disease had moderately elevated TG with controlled LDL-C, identifying an increased event rate in these patients compared to those with TG <1.0 mmol/l. 5 Prescribing of HI-statins was considerably lower amongst patients with LDL-C levels above target. Whilst it is possible that a proportion of these patients were intolerant of HI-statins, it is more likely that a greater proportion of patients prescribed NI-statins with uncontrolled LDL-C, would be tolerant of HI-statins, acknowledging prior reported levels of statin intolerance in just 10-20% of statin-treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the CLARIFY registry, 22 which involved patients with stable coronary artery disease (defined as a history of myocardial infarction, coronary stenosis >50%, symptomatic myocardial ischemia, or previous coronary revascularization procedure), 15.5% would have broadly met the enrolment criteria for REDUCE‐IT. One‐quarter of the ONTARIO study 23 population were reported to be eligible, but the population was broad based and included patients with a history of myocardial infarction, ischemic stroke, peripheral artery disease, or previous coronary revascularization procedure. The most similar study to FAST‐MI was a population‐based Danish cohort study in patients with myocardial infarction, 25 in which 21% met the enrolment criteria for REDUCE‐IT, substantially more than those in the FAST‐MI registries.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have applied the REDUCE-IT enrolment criteria to their study populations. [22][23][24][25] In the Veterans Affairs healthcare system, 24 14.5% of the population with ASCVD (defined as a history of myocardial infarction, ischemic stroke, or peripheral artery disease)…”
Section: Methodsmentioning
confidence: 99%